Intersecting Journeys the Anthropology of Pilgrimage and Tourism. - Badone, Ellen (University of Illinois Press, 2004)
The appeal of sacred sites remains undiminished at the start of the twenty-first century, as unprecedented numbers of visitors travel to Lourdes, Rome, Jerusalem, Santiago de Compostela, and even Star Trek conventions. Ethnographic analysis of the conflicts over resources and meanings associated with such sites, as well as the sense of community they inspire, provides compelling evidence re-emphasizing the links between pilgrimage and tourism. As the papers in this collection demonstrate, studies of these forms of journeying are at the forefront of postmodern debates about movement and centers, global flows, social identities, and the negotiation of meanings.
Cover -- Contents -- Acknowledgments -- 1. Approaches to the Anthropology of Pilgrimage and Tourism -- 2. "They Told What Happened on the Road": Narrative and the Construction of Experiential Knowledge on the Pilgrimage to Chimayo, New Mexico -- 3. Pilgrimage to "England's Nazareth": Landscapes of Myth and Memory at Walsingham -- 4. Santiago de Compostela in the Year 2000: From Religious Center to European City of Culture -- 5. Stories of the Return: Pilgrimage and Its Aftermaths -- 6. Tourism and Holy Week in Leon, Spain -- 7. The Kyoto Tax Strike: Buddhism, Shinto, and Tourism in Japan -- 8. Extending the Metaphor: British Missionaries as Pilgrims in New Guinea -- 9. Pilgrimage and the IDIC Ethic: Exploring Star Trek Convention Attendance as Pilgrimage -- 10. Crossing Boundaries: Exploring the Borderlands of Ethnography, Tourism, and Pilgrimage -- Contributors -- Index.
Keywords: Pilgrims and pilgrimages; Culture and tourism; POLITICAL SCIENCE / Public Policy / Cultural Policy; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Popular Culture; Electronic resource; Electronic books